2014
DOI: 10.1089/cyber.2012.0497
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Experiments Linking Social Environment and Psychosis: A Pilot Study

Abstract: Initial studies with healthy subjects and individuals with high risk for psychosis have suggested that virtual reality (VR) environments may be used to investigate social and psychological mechanisms of psychosis. One small study reported that VR can safely be used in individuals with current persecutory delusions. The present pilot study investigated the feasibility and potential negative side effects of exposure to different virtual social risk environments in patients with first episode psychosis and in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 22 publications
1
66
0
4
Order By: Relevance
“…Moreover, lower perceived social rank has been found to be associated with paranoid ideation in healthy controls (Freeman et al, 2005;Gilbert et al, 2005) and in people with early psychosis (Allison et al, 2013), and paranoia in real life has been found to be associated with VR related paranoid ideation in VR in people with psychosis (Veling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, lower perceived social rank has been found to be associated with paranoid ideation in healthy controls (Freeman et al, 2005;Gilbert et al, 2005) and in people with early psychosis (Allison et al, 2013), and paranoia in real life has been found to be associated with VR related paranoid ideation in VR in people with psychosis (Veling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, research using virtual reality to study in vivo and in situ reactions to social situations allows the measurement of real-time physiological activation and the assessment of thoughts, mood and symptoms as they occur(e.g. (Fornells-Ambrojo et al, 2013;Freeman et al, 2005;Freeman et al, 2003;Stinson et al, 2010;Valmaggia et al, 2007;Veling et al, 2014)). …”
Section: Introductionmentioning
confidence: 99%
“…Psychotic symptoms can be evaluated in a more standardised way by using a Virtual Reality (VR) environment, which provides an ecologically valid and controlled setting that can elicit paranoid experiences (Freeman et al, 2005. VR environments such as a busy train carriage have been shown to induce paranoid ideation in healthy participants (Freeman et al, 2003, Green et al, 2011, people at UHR for psychosis , and individuals with persecutory delusions (Fornells-Ambrojo et al, 2008, Veling et al, 2014. The environmental stimulus is identical in all participants, and their response can be evaluated as soon as they exit the environment, maximising the likelihood of obtaining an accurate assessment of their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Galvanic skin response, heart rate and behavioural response (distance kept from the avatars) was found to be triggered by changes in population density and ethnic density in a VR bar environment [ 69 ]. The same environment was used to investigate galvanic skin response in a sample of individuals with psychosis [ 65 ]. Distance kept from the avatar was also measured in a study which manipulated the contingency behaviour of avatars while participants were exploring a VR student flat [ 60 ].…”
Section: Physiological Activation and Behavioural Responsementioning
confidence: 99%